The microbiology of safe food - Forsythe, S. J. [ (Steve J.)] (Blackwell Publication, 2010)
Food production is a complex and global enterprise, and public awareness of poisoning outbreaks is higher than ever. This book reviews the production of food and the level of microorganisms that humans ingest, covering both food pathogens and food spoilage organisms. It contains information on the microbiological issues of concern in food safety.